2018
DOI: 10.1002/pssa.201800160
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Light and Elevated Temperature Induced Degradation in Multicrystalline Silicon Wafers and PERC Solar Cells Using Phosphorus Diffusion Gettering

Abstract: Reducing light and elevated temperature induced degradation (LeTID) is important for the industrial success of PERC (passivated emitter and rear cell) solar cells fabricated on high-performance multicrystalline silicon (multi-Si) wafers. Although there has been a lot of progress in understanding the degradation kinetics, the defect(s) responsible for LeTID in multi-Si wafers at elevated temperatures (%80 C, 1 Sun) has yet to be identified. In this study, the authors look at the possibility of using phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Zuschlag et al showed that P‐diffused SiN x ‐passivated mc‐Si lifetime samples experienced only slight degradation, whereas a stronger and faster LeTID was observed in ungettered sister samples . Chakraborty et al presented similar results and reported that phosphorus diffusion gettering reduced the concentration of light‐induced defects, which were suspected to be Cu, Ni, and Ti, by nearly one order of magnitude . Interestingly, our previous study demonstrated that heavy phosphorus‐doping in the b‐Si spikes after an industry‐typical POCl 3 diffusion process enhances iron segregation to the emitter, which substantially improves minority carrier lifetime in iron‐contaminated substrates .…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Zuschlag et al showed that P‐diffused SiN x ‐passivated mc‐Si lifetime samples experienced only slight degradation, whereas a stronger and faster LeTID was observed in ungettered sister samples . Chakraborty et al presented similar results and reported that phosphorus diffusion gettering reduced the concentration of light‐induced defects, which were suspected to be Cu, Ni, and Ti, by nearly one order of magnitude . Interestingly, our previous study demonstrated that heavy phosphorus‐doping in the b‐Si spikes after an industry‐typical POCl 3 diffusion process enhances iron segregation to the emitter, which substantially improves minority carrier lifetime in iron‐contaminated substrates .…”
Section: Resultssupporting
confidence: 87%
“…Recent studies suggest that P or Al‐gettering can suppress LeTID to some extent, especially in material with low lifetime . Zuschlag et al showed that P‐diffused SiN x ‐passivated mc‐Si lifetime samples experienced only slight degradation, whereas a stronger and faster LeTID was observed in ungettered sister samples .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations